Insight into the in silico study and biological evaluation of curcumin analogue compounds as new potential inhibitors for dengue DEN2 NS2B/NS3 serine protease - Frimayanti, Neni; Herfindo, Noval; Siti Aisyah,; Rahmawaty, Eni Nur (Penerbit Universiti Kebangsaan Malaysia, 2024)
Dengue is an infectious disease caused by a virus and it is a rapidly emerging pandemic disease in many parts of the world. However, to date, one licensed tetravalent Dengvaxia vaccine based on a yellow fever virus vaccine variant has been reported. In silico and biological assay were performed to twenty two curcumin analogue compounds with DEN2 NS2B/NS3 serine protease as target. The main purpose of this study were to predict and estimate the binding interaction and also the ability of curcumin analogue compounds to be potential inhibitors for DEN2 NS2B/NS3. Computational pipeline such as molecular docking and molecular dynamic were constructed to get insight into potential inhibitor for DEN2 NS2B/NS3. Biological assay was performed to validate in silico results. Docking results reported that compounds 3, 10, and 13 have the lowest binding free energy value of -15.2 kcal/mol, -13.66 kcal/mol and -13.68 kcal/mol, respectively. All these three compounds were also able to interacts with Lys74 (i.e., allosteric site of serine protease) through hydrogen bonding, these binding is keep maintain during the molecular dynamic simulation. Among all of the compounds tested on their percent inhibition against DEN2 NS2B/NS3, compounds 3, 10, and 13 exhibited the best of percent inhibition. Thus, three of these compounds can be used as potential candidate for the next stage in the drug discovery process.